Magnetic molecularly imprinted polymers for recognition and enrichment of polysaccharides from seaweed. Issue 24 (13th November 2017) - Li, Guizhen; Row, Kyung Ho
Abstract: New magnetic molecularly imprinted polymers with two templates were fabricated for the recognition of polysaccharides (fucoidan and alginic acid) from seaweed by magnetic solid‐phase extraction, and the materials were modified by seven types of deep eutectic solvents. It was found that the deep eutectic solvents magnetic molecularly imprinted polymers showed stronger recognition and higher recoveries for fucoidan and alginic acid than magnetic molecularly imprinted polymers, and the deep eutectic solvents‐4‐magnetic molecularly imprinted polymers had the best effects. The practical recovery of the two polysaccharides (fucoidan and alginic acid) purified with deep eutectic solvents‐4‐magnetic molecular imprinted polymers in seaweed under the optimal conditions were 89.87, and 92.0%, respectively, and the actual amounts extracted were 20.6 and 18.7 μg/g, respectively. To sum up, the developed method proved to be a novel and promising method for the recognition of complex polysaccharide samples from seaweed.